Lost Narratives and Hybrid Identities in the Indian Ocean: Afro-Asians - Shihan de Silva (Universitat Autònoma de Barcelona, 2017)
The voluntary movement of Africans was concurrent with the involuntary uprooting of these peoples, driven by the slave trade. Trade, colonisation and slavery have been drivers of migration, interconnecting people of diverse ethnicity globally.  We assure that Afro-Asian communities are both historic and contemporary and, whilst Afro-diasporic communities in the Atlantic World are well recognised, the diasporas in Asia have only become visible in the last decade.  Assimilation to the diversity of the Indian Ocean has contributed to this invisibility.  With the loss of patronage due to changing political scenarios, African migrants have become disenfranchised. The dynamics of their identity, shaped by strong cultural memories bring out their African roots.  This paper argues that diasporic consciousness of Afro-Asians is expressed through their strong cultural memories.  As people with dual belongings, identifying with both the homeland and the hostland, Afro-Asians are able to reconcile their hybrid identities. With the movement of Afro-Asians from the peripheries their subaltern voices are beginning to be heard.  Their eclipsed histories and lost narratives are challenging the Atlantic model of African migration.